Can subalterns sing? Kalmyk songs about their exile to Siberia - E.-B. M. Guchinova; T. B. Seleeva (Шаги, 2024)
The article deals with Kalmyk folk songs about the deportation of the Kalmyk people to Siberia (1943–1957). The purpose is to exhibit the Siberian cycle of Kalmyk songs as a special genre, to elucidate its folklore specifics and to show how its pragmatics have changed depending on the political context during the last 80 years. The study is based on a corpus of 80 texts in the Kalmyk language. The songs were collected among folk song performers in Kalmykia, and from archival recordings, social networks and published songs. The tradition of the Siberian song operates with its own fund of various types of constants and formulas. The article provides an analysis of plots, stylistics, reflections of small genres of folklore in song texts. Particular attention is paid to the pragmatics of Siberian songs in connection with the historical policy of the state, to the development of the performing canon and to the role of songs in the process of ethnic identification and collective memory. The songs of the Siberian cycle have a special role: these local voices became a vital source about the life and feelings of the Kalmyks in 1943–1957, as a kind of musical ego-documents reflecting the thoughts and feelings of the exiles: bewilderment, bitterness, resentment, hope. The authors show that the Siberian songs were the only public form of protest and a way to proclaim the suffering of the Kalmyks as a group.